Incontinentia pigmenti: a rare cause of skin rash in newborn - Bajaj, Upasana; Bhattacharjee, Prasun; Mishra, Keeranmayee; Trivedi, Pranay; Parashar, Ashwani (International Journal of Contemporary Pediatrics, 2024)
Incontinentia pigmenti (IP) is a genodermatosis caused by mutations in the NEMO gene (Xq28) and is lethal in males. It is an X-linked dominant disorder with multi-systemic involvement. It involves the central nervous system and ectodermal tissues like skin, teeth, hair, nails, eyes, and the commonest manifestations are cutaneous manifestations. Here we present a case of a female newborn with vesico bullous eruption presented at birth. A full-term newborn female patient born by LSCS presented at birth with multiple vesico bullous skin lesions over bilateral upper and lower limbs in a pattern consistent with Blaschko’s lines. Maternal HIV, HBsAg, VDRL, and TORCH screening were negative. Systemic examinations were normal. Supportive care and IV antibiotics with IV acyclovir were started but without any response. The sepsis screen, blood, and urine culture were negative. ANA was negative. Wound swab culture and skin culture were negative. Skin biopsy results showed eosinophilic infiltration of the dermis and spongiosis. Genetic testing could not be done. Topical steroids were prescribed. The diagnosis of Incontinentia pigmenti was established based on the patient’s skin lesions and biopsy results. The baby improved and was discharged on the 14th day of life on topical steroids and is currently under follow-up. Other dermatologic conditions, like mastocytosis and hereditary epidermolysis bullosa, should be considered in the differential diagnosis of Incontinentia pigmenti. The diagnosis of Incontinentia pigmenti should be confirmed by histopathological examination of biopsy specimens along with genetic testing. It is a systemic disorder, so clinical management should include a multidisciplinary approach.